Menormalkan yang Dianggap "Tidak Normal": Studi Kasus Penertiban Bahasa Isyarat Tunarungu di SLB Malang - Damaiati R. Kurnia; Thohari Slamet (Indonesian Journal of Disability Studies, 2016)
The diversity of Signs languages used by deaf depends on the local languages. to control those, the insist all special schools to use SIBI (Indonesian Syetem of Sign Language) sign languages as a form of normalization of the Deaf. Using qualitative research method with depht interviews many steakholders the research found that the policy of applying SIBIÂ  in all SLB of Malang city is based on the regulation of the minister of education and culture (Indonesia) No 0161/U/1994 on standardizing SIBI for the deaf. SIBI aimed to organize and standardize all local signs languages used by deaf. The government's policy has been pruposed as an effort of organizing the deaf to be obedient and useful in which these terms of obedient and useful here are addressed through normal ideology given by the teachers that SIBI appropriates to be used by the deaf as hearing people's language.Gradually deaf people reject that policy and propose new sign languages which coming from deaf cultures.